Serum infliximab concentrations and body mass index in patients with inflammatory bowel disease - de Nardi Marçal, Gustavo (2025)
Background: Inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), are chronic conditions associated with healthcare burdens. Advanced therapies, such as infliximab (IFX), have improved disease outcomes. However, the role of body mass index (BMI) in influencing IFX serum concentrations and treatment response remains unclear. Objective: This study aimed to evaluate the association between BMI and IFX serum concentrations during different disease activity phases. Materials and methods: This cross-sectional observational report categorized patients into eutrophic (BMI < 24.9 kg/m²) and overweight/obese (BMI ≥ 25 kg/m²) groups. Serum IFX concentrations were measured, and disease activity was assessed using clinical, laboratory, endoscopic, and/or radiologic criteria. Results: The analysis included 102 patients (80 with CD, 22 with UC). The median serum IFX concentration in eutrophic CD patients was 3.84 µg/mL (1.66–8.82), while in overweight/obese patients was 6.00 µg/mL (1.90–10.34), with no significant difference (p = 0.353). Among the 22 patients with UC, the median serum IFX concentration in eutrophic patients was 6.28 µg/mL (0.860–13.66), compared to 4.23 µg/mL (2.33–12.91) in overweight/ obese patients, with no significant difference (p = 0.920). No differences were found in IFX concentrations between patients in remission or active disease. Conclusions: this study did not confirm that BMI influences IFX concentrations. More studies are needed to explore the impact of BMI on IFX pharmacokinetics and therapeutic efficacy.